(untitled) (Historia, 2021)
That there is a flourish of literature on the fall of Robert Mugabe from power in November 2017 is not surprising. Mugabe was and still is a historical and political figure that invites the attention and curiosity of scholars and journalists alike. What is surprising is that some convenient accounts of the fall of Mugabe do more to conceal than reveal the complicity of some who write on Mugabe’s legacy of tyranny and political violence in Zimbabwe. Rigorous critiques of tyranny and tyrants that may lead to reflections on futures of democracy and freedom in such countries as Zimbabwe require courageous and critical scholars and journalist who are prepared to admit their own complicity, ideological and practical, in the cultivation and irrigation of tyrants. In The Graceless Fall of Robert Mugabe, Geoff Nyarota squanders an opportunity to stand amongst courageous writers that critique tyrants and also reflect on their own contribution to tyranny and despotism through their writings and political activism.